Pendapat Masyarakat Islam Terhadap Kristenisasi (Studi Kasus Di Perak Barat Surabaya) - Mahmud Muhsinin (Universitas Muhammadiyah Surabaya, 2019)
AbstractThe Protestant Christian movement which was very hostile to the Catholic Church succeeded in destroying the position of the Catholic Mission in India since the 17th century. But the French revolution had caused political upheaval in the Netherlands which resulted in the destruction of the Protestant Zending center and the revival of the Katoik Mission. as well as being very strong. After the Malacca peninsula was taken over by the Dutch and their power in Indonesia grew, the Catholic religion in Sulawesi was gradually taken over by the Dutch. namely in 1807, seven years later, in 1904, the center of the Catholic Mission in the Netherlands sent two delegates to Jakarta, Jacob Nellisen and Lambert Prinsen, then the mission was centered in Jakarta, Semarang and Surabaya.The purpose of this study include: to find out about the opinion of the Islamic community towards Christianization, how the relationship of the West Silver community between the Islamic Society and the Christian Community as well as how the religious attitude of the Islamic community towards Christians in the West Perak village.The results obtained are the views of the Islamic community towards Christianization can be mapped into 3 things: first the group of preachers: they argue that this movement must be dammed by preaching through three elements of preaching, namely: first: Charity of oral deeds, second: actualization of Islam with real works, third: praiseworthy personality as sokogurunya. The second group is ordinary people: they think religion is a personal belief that cannot be applied to others. The third group, namely: people who convert to Christianity but back again, they argue that religion cannot be related to ethnicity or family, it is a personal problem because one is free to choose the religion and belief that he believes. The relationship between the Islamic community and the Christian community is very tolerant and the religious attitude of the Islamic community towards Christians is to accept in worldly terms but not in religious or Shari'a matters. Keywords: Christianization, the opinion of the Islamic community towards Christianization.